Οὐκ τέχνη ἐστὶν ῥητορική: Sextus and the rhetorical crisis in the Roman Empire - Fortes, Fábio da Silva (Romanitas - Revista de Estudos Grecolatinos, 2014)
The refutation of Rhetorics under the late Pyrrhonic Ceticism has been extensively explained in literature. In this article, however, we present a different point of view regarding this subject: we aim at presenting within Rhetorics itself, taken as an educational and cultural practice in the Roman Empire, some aspects which pointed out the very crisis of which Sextus Empiricus is a remarkable representative. We evaluate positions within Seneca’s, Quintilian’s and Tacitus’s works, confronting them with Sextus Empiricus’s Against the rhetoricians.
Keywords: Ceticism; Rhetorics; Sextus Empiricus